1996
DOI: 10.1073/pnas.93.16.8194
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-mediated spatial segregation on individual polymeric support beads: application to generation and screening of encoded combinatorial libraries.

Abstract: Proteolysis of short NO-protected peptide substrates bound to polyoxyethylene-polystyrene beads releases selectively free amino sites in the enzyme-accessible "surface" area, The substantial majority of functional sites in the "interior" of the polymeric support are not reached by the enzyme and remain uncleaved (protected). Subsequent synthesis with two classes of orthogonal protecting groupsNa_tert-butyloxycarbonyl (Boc) and Na_9-fluorenylmethyloxycarbonyl (Fmoc)-allows generation of two structures on the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 20 publications
1
59
0
Order By: Relevance
“…This might have been partly due to the different synthesis procedures and limited accessibility of the reactive functional groups. It has been reported that (at most) 15% of the total amounts of functional groups of typical TentaGel beads are located on the surface of the bead (55). Moreover, protein immobilization on TentaGel was shown to be limited to the bead surface (2).…”
Section: Resultsmentioning
confidence: 99%
“…This might have been partly due to the different synthesis procedures and limited accessibility of the reactive functional groups. It has been reported that (at most) 15% of the total amounts of functional groups of typical TentaGel beads are located on the surface of the bead (55). Moreover, protein immobilization on TentaGel was shown to be limited to the bead surface (2).…”
Section: Resultsmentioning
confidence: 99%
“…Each bead has 100 pmol peptide conjugate (19). Columns containing beads were first blocked with 1% BSA in PBS for 30 min.…”
Section: Microbead Elisamentioning
confidence: 99%
“…This might be partially due to the different synthesis procedures and limited accessibility of the reactive functional groups. It has been reported that at most 15% of the total amount of functional groups of typical TentaGel beads are located on the surface of the bead [152]. Moreover, protein immobilization onto TentaGel was shown to be limited to the bead surface [153].…”
Section: Fig 26 CD Spectra Of Model Klal Peptide and Mk5e And Theimentioning
confidence: 99%
“…The comparably high MIC values of C-terminally immobilized KLAL and MK5E are likely related to the fact that the majority of these sequences (~ 75%; see ref. [152]) were tethered in the interior of the porous TentaGel S NH 2 and might not be accessible for membrane interaction [152,153]. Indeed, the small pore size of TentaGel S NH 2 [145] does not allow for bacterial entry and penetration.…”
Section: Antimicrobial Activity Of the Tethered Peptidesmentioning
confidence: 99%